Improving Quality Control in Cup Beverage Production Using the Six Sigma Method - Maryadi, Deri; Azrin, Amrillah; Suhendra, Suhendra (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
Purpose: This study aims to reduce defect rates and enhance operational efficiency in the cup beverage production process using the Six Sigma DMAIC methodology. Methodology: The research applies the DMAIC framework (Define, Measure, Analyze, Improve, Control) to identify key defect causes and implement process improvements. Results: The application of Six Sigma DMAIC significantly reduced defect rates, as evidenced by improved Defects Per Million Opportunities (DPMO) metrics. Findings: The study demonstrates the effectiveness of Six Sigma in improving process quality and reducing waste, leading to better operational performance and customer satisfaction. Originality: This research uniquely applies Six Sigma in the cup beverage production sector, showcasing its adaptability to this industry. Novelty: While Six Sigma has been widely used in various industries, its implementation in beverage production remains underexplored, making this study a valuable contribution. Conclusions: The Six Sigma DMAIC methodology effectively reduces defects, enhances process efficiency, and increases customer satisfaction. Type of Paper: Empirical research paper.